2018
DOI: 10.17796/1053-4628-42.3.6
|View full text |Cite
|
Sign up to set email alerts
|

Viability and Reproducibility of Periodontal Ligament Cells on Avulsed Teeth Stored in Ham's F-10 Solution

Abstract: Ham's F-10 is capable of preserving PDL cells viable and reproducible better than milk and tap water and similar to HBSS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…In the experimental studies, the teeth were typically allowed to dry for about 30 minutes (in mud or sand) to simulate the first aid situation prior to storing them in the solutions or films for 15 minutes to 24 hours. It is of note that only five experimental studies stored the extracted teeth for longer than 120 minutes 28–32 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the experimental studies, the teeth were typically allowed to dry for about 30 minutes (in mud or sand) to simulate the first aid situation prior to storing them in the solutions or films for 15 minutes to 24 hours. It is of note that only five experimental studies stored the extracted teeth for longer than 120 minutes 28–32 …”
Section: Resultsmentioning
confidence: 99%
“…Two studies reported on the effectiveness of tap water for storing an extracted tooth. One RCT including 30 extracted teeth for each comparison showed less benefit for cell viability after 60‐minute to 24‐hour immersion in tap water compared with milk 32 . One non‐RCT did not report the number of extracted teeth in the study groups but also showed that the extracted teeth stored in tap water for 45 minutes had a lower cell viability rate than those stored in milk 41 .…”
Section: Resultsmentioning
confidence: 99%
“…The First Aid Task Force requested a 2020 SysRev of media used to store an avulsed tooth until it can be reimplanted. 111 Many RCTs found benefit from immersion of the tooth in Hanks’ Balanced Salt Solution 146 , 147 , 148 , 149 , 150 , 151 , 152 , 153 , 154 , 155 , 156 , 157 as well as in oral rehydration salt solutions 154 , 155 or from wrapping the tooth in cling film (ie, plastic wrap) 158 as compared with immersion in milk. However, milk was better than many other media for storing a tooth until reimplantation.…”
Section: First Aidmentioning
confidence: 99%
“…We obtained 31 full texts to further verify their eligibility. After evaluating the full texts, 11 studies were excluded due to six reasons: ineligible topic (n = 5), no full text available (n = 1), duplicate records (n = 2), ineligible media (n = 1), ineligible outcome (n = 1), and inadequate data (n = 1), and then 20 eligible studies (6,(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41) including 31 reports were considered to be eligible for our inclusion criteria. The identification and selection of studies were Figure 1.…”
Section: Identification and Selection Of Studiesmentioning
confidence: 99%
“…Among the 20 included studies, only three studies (31,38,39) definitively reported the methods of generating random sequence, none of the studies (6,(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41) reported the details of performing allocation concealment, and all studies were rated as low risk of bias in incomplete data, selective reporting, and other bias domains. Overall, the level of risk of bias among all studies was considered to be moderate.…”
Section: Risk Of Biasmentioning
confidence: 99%